2007
DOI: 10.1021/ja069110h
|View full text |Cite
|
Sign up to set email alerts
|

A Density Functional Study of the 13C NMR Chemical Shifts in Functionalized Single-Walled Carbon Nanotubes

Abstract: The 13C NMR chemical shifts for functionalized (7,0), (8,0), (9,0), and (10,0) single-walled carbon nanotubes (SWNTs) have been studied computationally using gauge-including projector-augmented plane-wave (GIPAW) density functional theory (DFT). The functional groups NH, NCH3, NCH2OH, and CH2NHCH2 have been considered, and different sites where covalent addition or substitution may occur have been examined. The shifts of the carbons directly attached to the group are sensitive to the bond which has been functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 53 publications
7
52
0
Order By: Relevance
“…[29][30][31][32][33][34] 13 C NMR isotropic chemical shifts of pristine CNTs, based on the density functional theory (DFT) and an infinite CNT model, depend on the electronic structure and the diameter but not on the chirality. [31] It has also been demonstrated that a wealth of knowledge on functionalizations [32,34] and defects [33] of CNTs can be obtained from NMR simulations. Similarly, new insights about GO structure are expected to be obtain by a systematic computational NMR study.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34] 13 C NMR isotropic chemical shifts of pristine CNTs, based on the density functional theory (DFT) and an infinite CNT model, depend on the electronic structure and the diameter but not on the chirality. [31] It has also been demonstrated that a wealth of knowledge on functionalizations [32,34] and defects [33] of CNTs can be obtained from NMR simulations. Similarly, new insights about GO structure are expected to be obtain by a systematic computational NMR study.…”
Section: Introductionmentioning
confidence: 99%
“…Work on pristine periodic systems has also indicated that at least for small to medium diameter zigzag SWNTs the sp 2 -sp 3 rehybridization is not negligible and that NMR may perhaps be used to identify the diameter distribution within a homogeneous sample [78,80,81]. Finite SWNTs [70,79], infinite DWNTs [80,82], functionalized infinite SWNTs [96,111], and infinite SWNTs with StoneWales defects [124] have also been investigated. Table I summarizes 13 C chemical shifts and Knight shifts calculated for selected infinite and finite pristine SWNTs.…”
Section: Discussionmentioning
confidence: 99%
“…To theoretically study how the 13 C NMR chemical shifts of (n,0) SWNTs are affected by functionalization, we have carried out GIPAW DFT calculations of SWNTs functionalized with a N-R group (-R = organic ligand, N binds to the tube sidewall) [96,97]. Products typical of [2+1] cycloaddition and 1,3-dipolar cycloaddition reactions of an amine group to a SWNT sidewall were considered, so that the results could be compared with those from solution NMR studies where the tubes were derivatized with PEG 1500N [94].…”
Section: And 1 H Nmr Of Covalently Functionalized Single-walled Nanmentioning
confidence: 99%
See 2 more Smart Citations